2003
DOI: 10.1002/cncr.11573
|View full text |Cite
|
Sign up to set email alerts
|

Does retroperitoneal lymph node dissection have a curative role for patients with sex cord–stromal testicular tumors?

Abstract: BACKGROUND Sex cord–stromal tumors account for < 5% of all adult testicular tumors, and 10% are malignant. Due to the limited reported experience, there is no agreement on the best management, especially in patients who have tumors with malignant pathologic features or who present with metastatic disease. The authors attempt to evaluate the role of retroperitoneal lymph node dissection (RPLND) in the management of patients with these malignant sex cord–stromal tumors. METHODS Reviewing the Indiana University t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 14 publications
1
59
1
2
Order By: Relevance
“…Hanson and Ambaye have suggested that tumor size larger than 5 cm is a feature associated with malignancy in the testes. 5 Jimenez-Quintero et al considered size >7 cm, vascular or lymphatic invasion, and hemorrhage or necrosis somewhat predictive of spread. 6 Thus, follow-up for patients receiving radical orchiectomy should be extended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanson and Ambaye have suggested that tumor size larger than 5 cm is a feature associated with malignancy in the testes. 5 Jimenez-Quintero et al considered size >7 cm, vascular or lymphatic invasion, and hemorrhage or necrosis somewhat predictive of spread. 6 Thus, follow-up for patients receiving radical orchiectomy should be extended.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal lymph node dissection (RPLND) is also a treatment option for patients with lymph node metastasis in testicular germ cell tumor. Although the therapeutic role of RPLND is unclear, it is still an option after radical orchiectomy in aGrCT patients with malignant features, as described by Ashraf et al 5 Except surgical management, Jimenez-Quintero et al 6 suggested that etoposide based chemotherapy with adjuvant radiotherapy may be a curative option for metastatic disease. To date, in the absence of guidelines regarding aGrCT, it is difficult for urologists to implement a follow-up program.…”
Section: Discussionmentioning
confidence: 99%
“…11 Of these, four patients (31%) with clinical stage I disease were reclassified as pathological stage II following RPLND. None of the nine patients with pathologic stage I disease had recurrence after 4.5 years, but 6/8 patients with stage II or III disease died of disease progression, with a mean survival of 2.4 years.…”
Section: Scst: Detection and Interventionmentioning
confidence: 99%
“…Some "centres of excellence" support testes-sparing surgery in small tumours, while other centres routinely perform prophylactic retroperitoneal lymph node dissection (RPLND) after the initial radical orchiectomy. [4][5][6][7]11 Some centres have employed highrisk histological features in the orchiectomy specimen to riskstratify patients and identify those who may benefit most from RPLND, although none of these findings have been well validated. 8,[11][12][13][14] In addition, no data have been published to date regarding population-level characteristics of this malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation